Effect of RuO2 in the shape selectivity of submicron-sized SnO2 structures - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Journal of Physical Chemistry B, 2005)
Several dissimilar types of tin oxide microstructures including bipyramids, cubes, and wires synthesized effectively by means of a simple approach were investigated using X-ray diffraction (XRD), thermogravimetry/ differential thermometric analysis (TG-DTA), and X-ray photoelectron spectroscopy (XPS). A possible growth mechanism is proposed using the results of these studies. The texture coefficient values of all the structures, indexed to a tetragonal lattice, exhibit amazing variation in the preferred orientation with respect to their shapes. Although XPS data indicate that wires and cubes have a strong SnO2 type signal, bipyramids interestingly exhibit both SnO and SnO2 signals and a correlation of the binding energy helps in understanding the growth kinetics of such submicron structures. The. results suggest that the bipyramids are formed because of the vapor-solid process (VS) while wires and cubes are formed by the vapor-liquid-solid (VLS) progression.

Nanostructured tin oxide: synthesis and gas-sensing properties - Niranjan, R. S.; Hwang, Young Kyu; Kim, D. K.; Jhung, S. H.; Chang, J. S.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2005)
Pure and Ru-doped nanostructured SnO2 sensing materials were synthesized using a modified Pechini route. Incorporation of Ru in SnO2 results in the reduction of particle size (8.3 nm) compared with that of the pure SnO2 (28.2 nm). Moreover, the sensor exhibited a reasonably good sensitivity towards both H-2 and liquified petroleum gas (LPG). The effect of Ru incorporation, operating temperature, and gas concentration on the structure, morphology, and sensitivity is discussed using the results of X-ray diffraction (XRD), and scanning electron microscopy (SEM) along with sensing performance. © 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen and hydrocarbon sensor; Nanostructure; ruthenium; tin oxide

Room temperature nitric oxide sensor actualized from Ru-doped SnO2 nanowires - Ramgir, N. S.; Mulla, Imtiaz S.; Vijayamohanan, K. P. (Sensors and Actuators B - Chemical, 2005)
We report synthesis of the novel Ru-doped SnO2 nanowires and their distinctive response towards NO., and liquefied petroleum gas (LPG) in air. These nanowires have been prepared by a simple approach of evaporation of metal oxide at elevated temperature, The sensor exhibits three order of magnitude changes in the conductivity on exposure to NO2 in air at room temperature, Furthermore. Ru being one of the excellent sensitizers towards LPG these wires also exhibits sensitivity at 250&DEG; C. The amount of Ru plays a crucial role in modulating the sensitivity and lowering the operating temperature. © 2005 Elsevier B.V. All rights reserved.
Keywords: LPG; Nanowires; NO2; tin oxide ruthenium oxide

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Characterization of Cd1-xZnxSe thin films deposited at low temperature by chemical route - Hankare, P. P.; Chate, P. A.; Asabe, M. R.; Delekar, S. D.; Mulla, Imtiaz S.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2006)
Optoelectronic technologically important pseudo-binary Cd1-xZnxSe thin films with a variable composition ( 0 < x < 1) has been developed by chemical bath deposition method. The objective to study growth kinetics, physical, microscopic, compositional, optical, electrical and structural changes. Cd1-xZnxSe have been deposited on non-conducting glass substrate in tartarate bath containing Cd+2 and Zn+2 ions with sodium selenosulphate with an aqueous alkaline medium at 278 K. The quality and the thickness of the films are depends upon deposition temperature, deposition time and pH, etc. X-ray diffraction (XRD), atomic absorption spectroscopy, optical absorption, scanning electron microscopy and thermoelectric technique characterized the films. The XRD study indicates the polycrystalline nature in single cubic phase over whole range of composition. Analysis of absorption spectra gave direct type band gap, the magnitude of which increases non-linearly as zinc content in the film is increased and dc electrical conductivity at room temperature was found to decreases from 10(-7) to 10(-8) (Omega cm)(-1). All the films show n-type conductivity. The promising features observed are the formation of continuous solid solutions in a single cubic phase.

Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

Novel chemical synthetic route and characterization of zinc selenide thin films - Hankare, P. P.; Chate, P. A.; Delekar, S. D.; Asabe, M. R.; Mulla, Imtiaz S. (Journal of Physics and Chemistry of Solid, 2006)
Zinc selenide (ZnSe) thin film have been deposited using chemical bath method on non-conducting glass substrate in a tartarate bath containing zinc sulfate, ammonia, hydrazine hydrate, sodium selenosulfate in an aqueous alkaline medium at 333 K. The deposition parameter of the ZnSe thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption, electrical measurements, atomic absorption spectroscopy (AAS). The ZnSe thin layers grown with polycrystalline zinc blende system along with some amorphous phase present in ZnSe film. The direct optical band gap `E-g' for the film was found to be 2.81 eV and electrical conductivity in the order of 10(-8)(Omega cm)(-1) with n-type conduction mechanism. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: chalcogenides; electronic materials

Photoelectrochemical properties of electrochemically deposited CdIn2S4 thin films - Kokate, A. V.; Asabe, M. R.; Delekar, S. D.; Gavali, L. V.; Mulla, Imtiaz S.; Hankare, P. P.; Chougule, B. K. (Journal of Physics and Chemistry of Solids, 2006)
Thin films of CdIn2S4 have been deposited on to stainless steel and fluorine-doped tin oxide (FTO)-coated glass substrates from aqueous acidic bath using an electrodeposition technique. Ethylene diamine tetra-acetic acid (EDTA) disodium salt is used as complexing agent to obtain good-quality deposits by controlling the rate of the reaction. The different preparative parameters like concentration of bath, deposition time, bath temperature, pH of the bath have been optimized by the photoelectrochemical (PEC) technique in order to get good-quality photosensitive material. Different techniques have been used to characterize CdIn2S4 thin films. Optical absorption shows the presence of direct transition with band gap energy 2.17 eV. The X-ray diffraction (XRD) analysis of the as-deposited and annealed films showed the presence of polycrystalline nature. Energy-dispersive analysis by X-ray (EDAX) study for the sample deposited at optimized preparative parameters shows that the In-to-Cd ratio is almost 2 and S-to-Cd ratio is almost 4. Scanning electron microscopy (SEM) for samples deposited at optimized preparative parameters reveals that spherical grains are uniformly distributed over the surface of the substrate indicates the well-defined growth of polycrystalline CdIn2S4 thin film. PEC characterization of the films is carried out by studying photoresponse, spectral response and photovoltaic output characteristics. The fill factor (ff) and power conversion efficiency (eta) of the cell are 69 and 2.94%, respectively. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Thin films; X-ray diffraction

Suppression of electron-transfer characteristics of ferrocene by OTS monolayer on a silicon/electrolyte interface - Kulkarni, S. A.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, V. K. (Journal of Colloid and Interface Science, 2006)
The passivating behavior of self-assembled monolayers (SAMs) of octadecyltrichlorosilane (OTS) on an n-type Si(100) electrode with and without a redox species like ferrocene in a polar non-aqueous medium has been investigated using techniques like contact angle measurements, Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) to understand the role of the monolayer. The electron-transfer behavior of ferrocene is found to be drastically affected by the presence of monolayer and the reasons for these are analyzed as a function of the change in resistance, dielectric thickness and coverage of the monolayer. Electrochemical impedance analysis in the presence of ferrocene gives the monolayer coverage as 0.998 and the apparent rate constant calculated from this gives 4.85 x 10(-12) cm s(-1) in comparison with 4.4 x 10(-8) cm s(-1) for a similar electrode without any monolayer. A positive shift of 200 mV in the flat-band potential after monolayer formation also suggests the covalent coupling of the silane nionolayer offering a protective barrier. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: cyclic voltammetry; ferrocene; impedance analysis; octadecyltrichlorosilane (OTS); rate constant; self-assembled monolayer (SAM)

ZnO multipods, submicron wires, and spherical structures and their unique field emission behavior - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; More, Mahendra A.; Mulla, Imtiaz S.; Joag, Dilip S.; Vijayamohanan, K. (Journal of Physical Chemistry B, 2006)
A simple method of vapor deposition for the shape selective synthesis of ZnO structures, namely, multipods, submicron wires, and spheres, has been successfully demonstrated. A plausible growth mechanism based on the studies of scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) is proposed. Our studies suggest that the growth of a multipod structure is governed by the screw dislocation propagation while the vapor-liquid-solid (VLS) mechanism is responsible for the formation of submicron wires and spheres. Moreover, the flow rate of the carrier gas plays a crucial role in governing the morphology. Further, these structures exhibit an enhanced field emission behavior. The nonlinearity in the Fowler-Nordheim (F-N) plot, a characteristic feature of electron emission from semiconductors, is explained by considering the contributions from both the conduction and the valence bands of ZnO.

All-solid-state' electrochemistry of a protein-confined polymer electrolyte film - Parthasarathy, Meera; Pillai, Vijayamohanan K.; Mulla, Imtiaz S.; Shabab, Mohammed; Khan, Mohammad Islam (Biochemical and Biophysical Research Communications, 2007)
Interfacial redox behavior of a heme protein (hemoglobin) confined in a solid polymer electrolyte membrane, Nafion (a perfluoro sulfonic acid ionomer) is investigated using a unique `all-solid-state' electrochemical methodology. The supple phase-separated structure of the polymer electrolyte membrane, with hydrophilic pools containing solvated protons and water molecules, is found to preserve the incorporated protein in its active form even in the solid-state, using UV-visible, Fluorescence (of Tryptophan and Tyrosine residues) and DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy. More specifically, solid-state cyclic voltammetry and electrochemical impedance of the protein-incorporated polymer films reveal that the Fe2+-form of the entrapped protein is found to bind molecular oxygen more strongly than the native protein. In the `all-solid-state' methodology, as there is no need to dip the protein-modified electrode in a liquid electrolyte (like the conventional electrochemical methods), it offers an easier means to study a number of proteins in a variety of polymer matrices (even biomimetic assemblies). In addition, the results of the present investigation could find interesting application in a variety of research disciplines, in addition to its fundamental scientific interest, including protein biotechnology, pharmaceutical and biomimetic chemistry. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: all-solid-state; cyclic voltammetry; hemoglobin; Impedance; Nafion; redox behavior

Coprecipitation technique to prepare CoTa2O6 and CoNb2O6 - Mulla, Imtiaz S.; Natarajan, N.; Gaikwad, A. B.; Samuel, V.; Guptha, U. N.; Ravi, V. (Materials Letter, 2007)
An aqueous solution of sodium hydroxide was used to coprecipitate cobalt and tantalum (or niobium) ions from their precursors as hydroxides under basic conditions. This precipitate yielded CoTa2O6 (CT) or CoNb2O6 (CN) ceramics on calcining at 700 degrees C, i.e. at a temperature much lower than 900 degrees C, reported for the formation of these powders prepared by the traditional solid state method. The X-ray diffraction (XRD) studies were employed to investigate phase contents and lattice parameters. The morphology of the synthesized powders was investigated by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Oxides; X-ray methods

Energy analysis of field emitted electrons from a ZnO tetrapod - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Ramgir, Niranjan S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Applied Physics Letters, 2007)
The experimental total energy distribution (TED) of the field emitted electrons from a single pod of a ZnO tetrapod has been obtained, exhibiting a two-peak feature. The energy difference between the two peaks in the TED is found to be nearly equal to the band gap of the bulk ZnO. The results show that field emitted electrons originate from both the conduction and valence bands. The peak position dependence on the applied voltage has also been observed. In the present case, the size of the ZnO tetrapod is not small enough to reflect the quantum confinement effects.

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Low temperature synthesis and NOx sensing properties of nanostructured Al-doped ZnO - Navale, S. C.; Ravi, V.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2007)
Although ZnO is studied intensively as a sensing material, there are limited reports available on aluminum-doped ZnO (AZO) as a NO, sensor. This paper reports selective NO, sensing characteristics of M-doped ZnO synthesized in the form of porous pellets sintered at 350 degrees C. The salient feature of our experimental results is that our sensor can detect small concentrations of NO, at lower operating temperature. It is also observed that as compared to gases such as SOx HCl, LPG, H2S, H-2, ammonia, alcohol and acetone it selectively detects NOx due to Al-doping. The amount of Al in ZnO during synthesis is varied between 1 and 10 wt%. Our sensor senses NO, concentration as low as 20ppm at 100 degrees C with a %response of 11 and a %response of 740 at 300 degrees C for 1 wt% Al. Of all the compositions with Al-doping, I wt% is found to give best results. Sensing experiments carried out at 350 C, however. do not show any significant improvement in the gas sensing properties. The phase contents and lattice parameters were determined by XRD and the average particle size was obtained using Scherrer formula. A probable mechanism for sensing NO, involving oxygen ion adsorption and desorption on the surface of sensor has been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: aluminum doping; nanomaterial; NOx; Sensor; ZnO

Surface-state-mediated electron transfer at nanostructured ZnO multipod/electrolyte interfaces - Parthasarathy, Meera; Ramgir, Niranjan S.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
Redox kinetics of cyanoferrate(III) species adsorbed at an n-type ZnO multipod/electrolyte interface is explored using electrochemical techniques like cyclic voltammetry and impedance spectroscopy. The electrochemical impedance results are analyzed using a fluctuating energy level model, assuming isoenergetic tunneling of majority carriers through the Helmholtz layer. A shift in the slope of Mott-Schottky plots (C-sc(-2) versus E) together with evidence from cyclic voltammetry shows that the electron-transfer process is mediated by surface states formed because of the adsorption of ferricyanide ions (as evident from the results of Fourier transform infrared spectroscopy). More significantly, the pH of zero charge (point of zero zeta potential, pzzp) of ZnO multipods is found to be 4.5 (from capacitance vs pH plots) compared to that of bulk ZnO (pH 9.5), which could be explained on the basis of a lowering in the work function of the nanostructured semiconductor and its consequent susceptibility to the formation of surface states. This is in excellent agreement with our earlier observation of ultralow threshold field emission with this material in the light of the linear dependence of pzzp with work function of the electrode material. The flat-band potential of the nanostructures is found to be 200 mV more negative than that reported for bulk n-type ZnO electrodes, indicating a higher doping density in the former. A three-dimensional mapping of charge distribution in the surface states is attempted by correlating the capacitance response of the system subjected to a sinusoidal potential modulation to the semiconductor electrode with that resulting from a systematic variation of the redox potential of the dissolved acceptor (achieved by varying the pH of the electrolyte) which further reveals the polyenergetic nature of the surface states.

Template-assisted synthesis of ruthenium oxide nanoneedles: electrical and electrochemical properties - Subhramannia, Mahima; Balan, Beena K.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
We here demonstrate the formation of bundles of RuO2 nanoneedles (ca. 100 nm diameter) by a templateassisted electrodeposition from aqueous RuCl3 solution under potentiostatic conditions at room temperature. Cyclic voltammetric measurements in 0.5 M H2SO4 show significantly higher redox-related charging behavior for the RuO2 nanoneedles compared to that of the commercial sample, which is also supported by the electrochemical impedance data. A comparison of the specific capacitance reveals a higher value for nanoneedles (3 F/g instead of 0.4 F/g for the bulk), which has been explained on the basis of enhanced reactivity. More interestingly, electrical transport measurements reveal a transition from metallic to semiconducting behavior especially at low-temperature caused by an impurity scattering mechanism. We anticipate that the present simple route for the fabrication of RuO2 nanostructures will be useful to exploit their potentials in various fields such as electrocatalysis, nanoelectronics, and more importantly for designing supercapacitors.

Characterization of MoSe2 thin film deposited at room temperature from solution phase - Hankare, P. P.; Patil, A. A.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Manikshete, A. H.; Mulla, Imtiaz S. (Journal of Crystal Growth, 2008)
A simple, low-temperature method has been developed to synthesis molybdenum diselenide semiconductor thin films, based on the chemical reaction of conlplexed ammonium molybdate, hydrazine hydrate and sodium Selenosulphate in aqueous alkaline medium. The deposition parameter of the MoSe2 thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption and electrical measurements. The deposited film was found to be polycrystalline in hexagonal form. The direct band gap `E-g' for the film was found to be 1.43eV and electrical conductivity in the order of 10(-2)(Omega cm)(-1) with n-type conduction mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from solution; Inorganic compound; Polycrystalline deposition; Semiconducting materials; X-ray diffraction

Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

Effect of synthesis procedure on the structure and properties of palladium/polycarbonate nanocomposites - Valmikanathan, O. P.; Ostroverkhova, O.; Mulla, Imtiaz S.; Vijayamohanan, K.; Atre, S. V. (Polymer, 2008)
In this paper, we compare two procedures for the synthesis of palladium (Pd)/polycarbonate (PC) nanocomposites as well as their morphological, optical, thermal and electrical properties. Pd nanoclusters were produced by the reduction of palladium chloride using a variation of Brust's method. Discrete I'd nanoclusters of similar to 15 nm size were formed in the absence of PC in the reaction mixture (ex situ method) while agglomeration of Pd nanoclusters was noticed in the presence of PC in the reaction mixture (in situ method). Fourier transform infrared spectroscopy (FTIR) suggests nanoparticle-polymer interactions and polymer conformational changes in the in situ nanocomposite films. Even after having the same Pd content, the ex situ nanocomposites films were found to transmit more light than the in situ nanocomposites. The glass transition temperature (T-g), decreased by similar to 16 degrees C for both the ex situ and in situ samples. Thermogravimetric analysis (TGA) indicated that the presence of Pd nanoclusters significantly improved the thermal stability of the nanocomposites, as evidenced by the enhanced onset of degradation by similar to 20 degrees C and similar to 40 degrees C for the in situ and ex situ nanocomposites, respectively. The electrical conductivity measurement shows a dramatic difference between these nanocomposites with a significantly higher value for the in situ nanocomposite (resistivity = 2.1 X 10(5) Omega m) compared to the ex situ nanocomposite (resistivity = 7.2 x 10(13) Omega m). (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: in situ and ex situ syntheses; Morphology; Nanocomposites

Electrochemical sensing of sulphur dioxide: a comparison using dodecanethiol and citrate capped gold nanoclusters - Sathe, Bhaskar R.; Risbud, Mandar S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Nanoscience and Nanotechnology, 2008)
A comparison of cyclic voltammograms of dodecanethiol (DDT) capped Au nanoclusters (5.0 +/- 0.5 nm) and trisodium citrate (Cit) capped Au nanoclusters (similar to 10-15 nm) modified glassy carbon electrode shows a dramatic variation in the current when exposed to a small amount of sulphur dioxide. This is explained using the electrocatalytic properties of Au nanoclusters towards the oxidation of SO2, thus facilitating the fabrication of electrochemical sensors for the detection of SO2. The intrinsic redox changes observed for gold nanocluster-modified glassy carbon electrodes disappear on passing SO2, despite a dramatic current increase, which indeed scales up with the amount of dissolved SO2. Interestingly, a complete rejuvenation of the redox behavior of gold is also observed on subsequent removal of SO2 from the solution by passing pure nitrogen for 15 minutes. Further, these nanoclusters when characterized with X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) after SO2 passage reveal a variety of SO2 adsorption modes on gold surface. XP spectra also show a shift of 1.03 eV towards higher binding energy indicating a strong adsorption of SO2 gas, while FTIR gives conclusive evidence for the interaction of SO2 with gold nanoparticles.
Keywords: cyclic voltammetry; Fourier transform infrared spectroscopy; monolayer protected gold nanoclusters (Au-MPCs); SO2 sensor; X-ray photoelectron spectra

Enhanced field emission from hexagonal rhodium nanostructures - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Late, Dattatray J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2008)
Shape selective synthesis of nanostructured Rh hexagons has been demonstrated with the help of a modified chemical vapor deposition using rhodium acetate. An ultralow threshold field of 0.72 V/mu m is observed to generate a field emission current density of 4 x 10(-3) mu A/cm(2). The high enhancement factor (9325) indicates that the origin of electron emission is from nanostructured features. The smaller size of emitting area, excellent current density, and stability over a period of more than 3 h are promising characteristics for the development of electron sources. (C) 2008 American Institute of Physics.

EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO

Facile synthesis and gas sensing properties of nanotriangular tin oxide - Deshmukh, Rupali G.; Badadhe, Satish S.; Vaishampayan, Mukta V.; Mulla, Imtiaz S. (Materials Letters, 2008)
In the present study we report a simple and convenient chemical route using pentaerythritol as a structure-directing agent for the synthesis of crystalline nanotriangular SnO2. We propose the scheme for the formation of nanotriangular structures wherein the preliminary spherical nanocrystallites are formed due to the low surface energy associated with them. These spherical nanocrystallites grow into the various linear intermediate shapes like Y, bi and tripods, which finally lead to the triangles, pyramids and bipyramids. Such variation in the structure occurs due to the structure directing pentaerythritol. These polycrystalline SnO2 nanomaterials with structural peculiarities were tested for the gas sensing characteristics. Their response towards ethanol vapor, H-2 and LPG were investigated. It was found to exhibit high response towards ethanol vapors at the operating temperature of 250 degrees C. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Nanomaterials; Oxides; Semiconductors; sensors

Fe-doped SnO(2) nanomaterial: a low temperature hydrogen sulfide gas sensor - Vaishampayan, Mukta V.; Deshmukh, Rupah G.; Walke, Pravin; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2008)
The effect of Fe-doping on the surface chemistry and gas-sensing properties of nanocrystalline tin oxide is analyzed. The pristine and Fe-doped SnO(2) are synthesized by the modified Pechini citrate route that produces around 40 and 18 nm sized nanoparticles, respectively. 1 at.% Fe-doped SnO(2) shows significantly high selectivity towards hydrogen sulfide gas with capability to detect even 10 ppm of hydrogen sulfide at room temperature, with change of about one order of magnitude in the resistance within 5-15 s. In comparison, pristine SnO(2) shows negligible response towards H(2)S at room temperature. The ideal response and recovery of Fe-doped SnO(2) at low concentration of gas suggests Fe-doped SnO(2) nanomaterial as a potential low cost, low temperature H(2)S gas sensor. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Fe-doping; H(2)S; nanomaterial; Sensor; tin oxide

Gas-sensing properties of zinc ferrite nanoparticles synthesized by the molten-salt route - Darshane, Sonali L.; Deshmukh, Rupali G.; Suryavanshi, Shankar S.; Mulla, Imtiaz S. (Journal of the American Ceramic Society, 2008)
Zinc ferrite (ZnFe2O4) nanoparticles have been synthesized at 700 degrees C using sodium chloride as a growth inhibitor. Single-phase formation of spinel zinc ferrite having crystallite size in the range of 15-20 nm was observed by XRD and confirmed by TEM. In the present work, the gas-sensing properties of these zinc ferrite nanoparticles toward ethanol, LPG, H-2, NOx. SOx, and H2S have been studied. It was found that they exhibit excellent selective sensitivity toward 200 ppm of H2S at the operating temperature of 250 degrees C, and thus this nanosized ferrite is expected to be useful in an industrial application as a potential H2S gas sensor.

Influence of Pd doping on morphology and LPG response of SnO2 - Vaishampayan, Mukta V.; Deshmukh, Rupali G.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2008)
In the present study nanocrystalline pristine and Pd-doped SnO2 (Pd:SnO2) with various mol% Pd have been synthesized by a modified Pechini citrate route. Transmission electron microscopy and X-ray powder diffraction studies were used to characterize the morphology, crystallinity, and structure of the SnO2 and Pd:SnO2. The response of the pristine SnO2 and Pd:SnO2 was studied towards different reducing gases. The 1.5 mol% Pd doping showed an enhanced response of 75 and 95% towards LPG at as low as 50 and 100 degrees C, respectively, which were quite large high value as compared with pristine SnO2 (38 and 35% at 50 and 100 degrees C, respectively). Structural characterization revealed that Pd doping reduced the crystallite size of SnO2 and helps in the formation of distinct spherical nanospheres at a calcinations temperature of 500 degrees C. Thus the increase in LPG response can be correlated with the spherical morphology, a decrease in the crystallite size (11 nm) due to doping with Pd as compared with the pristine SnO2 (26 nm) and main role of Pd as a catalyst. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: LPG sensor; nanospheres; palladium doping; tin oxide

Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

RuO(2) doped SnO(2) nanobipyramids on Si (100) as a field emitter - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Thin Solid Films, 2008)
Thin films of RuO(2): SnO(2) nanobipyramids have been grown on silicon (100) flat substrates, and their field emission behavior has been investigated. The field emission experiments have been performed in parallel plate configuration. In this experiment, the onset field for 0. 1 gA/ cm 2 current density has been found to be 0.2 V/mu m. The Fowler-Nordheim plot shows non-linear nature typical that of a semiconductor. The field enhancement factor has been estimated to be 35,600 cm(-1), indicating that the field emission originates from the nanometric features of the emitter. The current stability recorded at a preset value of I tA is observed to be good. Our field emission results on RuO(2): SnO(2) nanobipyramids indicate that, RuO(2): SnO(2) nanobipyramids are a potential candidate for futuristic field emission based devices. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emitter; field enhancement factor; ruthenium oxide; tin oxide

Synthesis, characterization of chemically deposited indium selenide thin films at room temperature - Asabe, M. R.; Chate, P. A.; Delekar, S. D.; Garadkar, K. M.; Mulla, Imtiaz S.; Hankare, P. P. (Journal of Physics and Chemistry of Solids, 2008)
Polycrystalline In2Se3 semiconducting thin films were prepared by using relatively simple chemical bath deposition method at room temperature by the reaction between indium chloride, tartaric acid, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium. Various preparative conditions of thin film deposition are outlined. The as grown films were found to be transparent, uniform, well adherent and red in color. The films were characterized using X-ray diffraction (XRD), scanning electron microscopy, atomic absorption spectroscopy and energy dispersive atomic X-ray diffraction (EDAX). The XRD analysis of the film showed the presence of polycrystalline nature with hexagonal crystal structure. SEM study revels that the grains are homogenous, without cracks or pinholes and well covers the glass substrate. The optical absorption and electrical conductivity was measured. The direct optical band gap value for the films was found to be of the order of 2.35eV at room temperature and have specific electrical conductivity of the order of 10(-2) (Omega cm)(-1) showing n-type conduction mechanism. The utility of the adapted technique is discussed from the view-point of applications considering the optoelectric and structural data. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Semiconductor

Effect of sintering temperature and thermoelectric power studies of the system MgFe2-xCrxO4 - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Gavali, L. V.; Sasikala, R.; Mulla, Imtiaz S. (Solid State Sciences, 2009)
Mixed metal oxides showing the spinel structure exhibit interesting structural and electrical properties. Substances with specific compositions in the system MgFe2-xCrxO4 were synthesized by the simple co-precipitation method and have been investigated by X-ray diffraction (XRD) and scanning electron microscope (SEM) to study the effect of temperature on the size of particles and grains. The infrared spectrum shows, two strong bands around 600 and 500 cm(-1). An elemental composition of one of the samples, MgFeCrO4 was found by energy dispersive X-ray spectroscopy (EDS). The thermoelectric power measurements carried out from room temperature to 500 degrees C, show both n-type and p-type behavior. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: synthesis; Temperature effect; Thermoelectric studies

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Gas sensing properties of magnesium ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Patil, R. P.; Sasikala, R.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2009)
Polycrystalline magnesium ferrite (MgFe(2)O(4)) was prepared by the co-precipitation method. The synthesized compound was characterized for their phase and morphology by X-ray diffraction and scanning electron microscopy, respectively. Conductance responses of the (MgFe(2)O(4)) were measured towards gases like hydrogen sulfide (H(2)S), liquefied petroleum gas (LPG), ethanol vapors (C(2)H(5)OH), SO(x), H(2), NO(x), NH(3), methanol, acetone and petrol. The gas sensing characterstics were obtained by measuring the sensitivity as a function of various controlling factors like operating temperatures and concentrations of gases. It was found that the sensor exhibited various responses towards these gases at different operating temperatures. Furthermore; the MgFe(2)O(4) based sensor exhibited a fast response and a good recovery towards petrol at temperature 250 degrees C. The results of the response towards petrol reveal that (MgFe(2)O(4)) synthesized by a simple co-precipitation method, would be a suitable material for the fabrication of the petrol sensor. (C) 2009 Published by Elsevier B.V.
Keywords: Ferrites; Gas sensor; X-ray diffraction and scanning electron microscopy

H(2)S gas sensitive indium-doped ZnO thin films: preparation and characterization - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
High quality indium-doped ZnO (IZO) thin films (similar to 100 nm) have been deposited onto the glass substrates by using a conventional spray pyrolysis technique. Precursors such as zinc acetate, indium chloride with Brij-35 (polyoxyethylene lauryl ether) as a non-ionic surfactant were used. The morphology, crystal structure, elemental analysis and the gas response properties were investigated by using SEM, TEM, XRD, AFM and XPS techniques. The films show hexagonal wurtzite structure which reveal variations in (100). (00 2) and (10 1) intensities with indium doping. The crystallite size calculated by Scherrer formula was in the range of 30-50 nm. The SEM and AFM analysis show 50-70 nm sized grains, while the TEM confirms formation of grains by similar to 10nm sized particles. Their response towards various gases was measured at different operating temperatures and different levels of In-dopants. The 3 at% In-doped ZnO showed response as high as 13,000 for 1000ppm H(2)S at 250 degrees C. It exhibited fast response (similar to 2s) and recovery time (similar to 4 min). The gas response strongly depends on the morphology and indium concentration. The high gas response of IZO is explained on the basis of thickness dependent trap state density. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Hydrogen sulfide sensor; Indium oxide; Spray pyrolysis; thin film; Zinc oxide

Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide

Investigations on Ru doped ZnO: strain calculations and gas sensing study - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
Pure and ruthenium (Ru) doped nano-crystalline zinc oxide (ZnO) powders were synthesized by using well-known citrate gel route. Citric acid acts as a chelating agent and thus helps in the formation of nanoparticles. The detailed X-ray diffraction (XRD) studies using Hall equation reveal that in the nanoscale dimensions, incorporation of Ru modulates the lattice strain. It is interesting to note that on Ru doping, the compressive strain present in the undoped ZnO changes into tensile strain. We have tested the response of these specimens individually for reducing gases like H(2), LPG (liquefied petroleum gas), C(2)H(5)OH (ethanol), CO, acetone and oxidizing gases like NO, and Cl(2). Undoped ZnO responses perceptibly to LPG while Ru doped sample highly senses ethanol vapors. This might be due to either change in composition on Ru doping or/and difference between basicity of LPG and C(2)H(5)OH vapors. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Ethanol sensor; LPG sensor; Nanomaterials; ruthenium

Magnetic and dielectric properties of nanophase manganese-substituted lithium ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Jadhav, S. D.; Mulla, Imtiaz S.; Jadhav, K. M.; Chougule, B. K. (Journal of Magnetism and Magnetic Materials, 2009)
Nanocrystalline manganese-substituted lithium ferrites viz. Li0.5Fe2.5-xMnxO4 (2.5 <= x >= 0) were prepared by sol-gel autocombustion method. X-ray diffraction analysis confirmed that as the concentration of manganese increases the cubic phase changes to the tetragonal phase. The variation of saturation magnetization was studied as a function of manganese content. All the compositions indicate that they are ferrimagnetic in nature. The dielectric constant, dielectric loss tangent and ac conductivity of all samples were measured at room temperature as a function of frequency. These parameters decrease with increase in frequency for all of the samples. The substitution of manganese plays an important role in changing the structural and magnetic properties of these ferrites. The compositional variation of dielectric constant and d.c. resistivity shows an inverse trend of variation with each other. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Ferrite; Magnetization; X-ray diffraction

Microwave-assisted synthesis and humidity sensing of nanostructured alpha-Fe2O3 - Deshmukh, Rupali G.; Badadhe, Satish S.; Mulla, Imtiaz S. (Materials Research Bulletin, 2009)
Nanocrystalline alpha-Fe2O3 has been prepared on a large-scale by a facile microwave-assisted hydrothermal route from a solution of Fe(NO3)(3)center dot 9H(2)O and pentaerythritol. A systematic study of the morphology, crystallinity and oxidation state of Fe using different characterization techniques. Such as transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy was performed It reveals. that nanostructured alpha-Fe2O3 comprises bundles of nanorods with a rhombohedral crystalline Structure. The individual nanorod has 8-10 nm diameter and similar to 50 nm length. The as-prepared nanostructured alpha-Fe2O3 (sensor) gives selective response towards humidity. The sensor shows high sensitivity, fast linear response to change in the humidity with almost 100% reproducibility. The sensor works at room temperature and rejuvenates without heat treatment. The as-prepared nanostructured alpha-Fe2O3 appears to be a promising humidity sensing material with the potential for commercialization. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrical properties; Nanostructures; Oxides; X-ray diffraction

Nanostructured nickel ferrite: a liquid petroleum gas sensor - Darshane, Sonali L.; Suryavanshi, S. S.; Mulla, Imtiaz S. (Ceramics International, 2009)
The present investigation deals with the synthesis of nanostructured nickel ferrite (NiFe(2)O(4)) and their liquid petroleum gas-sensing characteristics. The 15-20 nm size nickel ferrite has been synthesized at 700 degrees C by a simple molten-salt route using sodium chloride as grain growth inhibitor. These nanoparticles exhibit significantly high response towards liquid petroleum gas (LPG) in comparison with ethanol vapor, hydrogen sulfide, ammonia and hydrogen. The gas response towards various gases at their 200 ppm concentrations is investigated at 200-450 degrees C. Different characterization techniques have been employed, such as differential thermal analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM) to study the crystallite size, structure and morphology. The results suggest possibility of utilization of the nanostructured nickel ferrite, without addition of any precious metal ion, as the LPG detector. (c) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrites; nanomaterial; Sensor; Spinels

Photoluminescence and gas sensing study of nanostructured pure and Sn doped ZnO - Navale, Shalaka C.; Mulla, Imtiaz S. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
The nanostructured pure and Sn doped ZnO have been synthesized by the thermal evaporation technique. The influence of Sri oil the morphology and structure is investigated by using scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analysis techniques, The SEM images indicate change in the growth pattern from nanowires of pure ZnO to tetrapods for Sn doped ZnO. Pure ZnO nanowires exhibit selective response towards acetone vapors while on Sri doping the response decreases. The non-stiochiometry and the morphology of ZnO arc probably responsible for such a difference in gas response. However increase in temperature doesn't improve the sensing behavior. The photoluminescence (PL) Studies reveal UV emission in pure ZnO which shifts to green emission oil doping of Sri. All rights reserved. (C) 2008 Elsevier B V. All rights reserved.
Keywords: Acetone; Gas sensors; Sn doped ZnO

Polymer-embedded stannic oxide nanoparticles as humidity sensors - Hatamie, Shadie; Dhas, Vivek V.; Kale, B. B.; Mulla, Imtiaz S.; Kale, Sangeeta N. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
Stannic oxide (SnO(2)) nanoparticles have been suspended in polyvinyl alcohol (PVA) matrix in different PVA: SnO(2) molar ratios ranging from 1:1 to 1:5 using simple chemical route. This suspension was deposited on ceramic substrate and upon drying was carefully detached from the substrate. SnO(2)-embedded self-standing, transparent and flexible thin films were hence synthesized. Transmission electron microscopy (TEM) and Xray diffraction (XRD) techniques show the rutile tetragonal structure of SnO(2) with particle size similar to 5 nm. UV-Visible spectroscopy demonstrates the band gap of 3.9 eV, which does not alter when embedded in polymer. Fourier transform infrared spectroscopy (FTIR) reveals that the properties of SnO(2) do not modify due to incorporation in the PVA matrix. The structures work as excellent humidity sensors at room temperature. For a critical PVA:SnO(2) molar ratio of 1:3, the resistance changes to five times of magnitude in 92% humidity within fraction of second when compared with resistance at 11% humidity. The sample regains its original resistance almost instantaneously after being removed from humid chamber. Nanodimensions of SnO(2) particles and percolation mechanism related to transport through polymer matrix and water molecule as a carrier has been used to understand the mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: humidity sensor; Nanoparticles; Polymer; Stannic oxide

Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction

Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures

Effect of Fe3O4 on morphology of Fe-SnO2 hyperbranched heterostructures - Sathe, Bhaskar R.; Walke, Pravin S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Chemical Physics Letters, 2010)
A simple modified thermal evaporation technique is employed for the synthesis of microstructured Fe:SnO2 system and their plausible growth mechanism has been proposed based on the results from various characterization techniques. Such structures grow in two steps; initially, growth of Fe core takes place from Fe3O4 source which acts as nucleating site for SnO2 growth on its surface as per the vapor-liquid- solid progression. Moreover, the composition of Fe/Sn source and temperature are found to have key roles in governing their morphology. XPS studies clearly demonstrate the presence of Fe species, which acts as a catalyst along with source for hetero-structure growth with SnO2. (C) 2010 Published by Elsevier B.V.

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures

Magnetic, dielectric and complex impedance spectroscopic studies of nanocrystalline Cr substituted Li-ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Garadkar, K. M.; Sasikala, R.; Tripathi, A. K.; Mulla, Imtiaz S. (Journal of Magnetism and Magnetic Materials, 2010)
Nanocrystalline Li0.5Fe2.5-xCrxO4 (2.5 <= x >= 0) ferrites were prepared by a sol-gel autocombustion route. X-ray diffraction was employed to confirm the cubic spinel phase formation of the ferrites. The lattice parameter decreases with increase in Cr content. The saturation magnetization, coercivity and remanance were studied as a function of Cr content. The dielectric constant and dielectric loss were measured as a function of frequency in the frequency range 20 Hz-1 MHz. Frequency dependence of dielectric constant shows dielectric dispersion due to the Maxwell-Wagner type of interfacial polarization. In order to understand the conduction mechanism, complex impedance measurements were carried out. The substitution of chromium plays an important role in changing the dielectric and magnetic properties of lithium ferrites. (C) 2010 Published by Elsevier B.V.
Keywords: Complex impedance; dielectric response; Ferrites; Magnetic hysteresis; Sol-gel synthesis; X-ray diffraction

Preparation and characterization of CuInSe2 thin films by chemical bath deposition technique - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2010)
Copper indium diselenide (CIS) thin films have been deposited using a precursor solution containing copper sulphate, indium trichoride, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium at room temperature. The as grown brown colored films were found to be well adherent to glass substrates. The films were characterized by X-ray diffraction, scanning electron microscopy, atomic absorption spectroscopy, optical absorption, electrical resistivity, and thermo electric measurement techniques. The analysis of optical absorption data shows band-gap energy (E-g) to be 1.1 eV. The electrical resistivity of the thin film was found to be of the order of 10(2) (Omega cm). Thermoelectric power measurement shows n-type conduction. (C) 2010 Published by Elsevier B.V.
Keywords: CuInSe2; Optical properties; Thin films; X-ray diffraction

Switching of hydrophilic to ultra hydrophilic properties of flower-like gold nanostructures - Dhumale, Vinayak A.; Shah, Preeti V.; Mulla, Imtiaz S.; Sharma, R. B. (Applied Surface Science, 2010)
Flower-like morphologies of gold nanostructures were obtained via chemical method by controlling molar concentration ratio of reducing agent and precursor. Chloroauric acid was used as a metal precursor while tri-sodium citrate as the reducing agent. These flower-like structures were characterized by UV-vis spectroscopy, Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD) techniques. The basic crystallite size calculated via XRD measurement was found to be similar to 10 nm and remain unaffected by the different concentration ratios. The coating of these structures was made over clean glass substrate and analyzed for wettability by measuring their water contact angles. Our analysis indicates that the coatings of hierarchical flower-like structures of gold are able to provide ultra hydrophilic properties to glass substrate. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Gold flower-like nanostructures; Ultra hydrophilic; Wettability

Synthesis and characterization of nanocrystalline zinc substituted nickel ferrites - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Sasikala, R.; Tripathi, A. K.; Garadkar, K. M. (Journal of Alloys and Compounds, 2010)
Nanocrystalline zinc substituted nickel ferrites, Ni(1-x)Zn(x)Fe(2)O(4) (0.0 <= x <= 1.0) have been prepared by citrate gel auto-combustion method. The effect of zinc ion content on structural, electrical transport and magnetic properties has been studied. The X-ray diffraction (XRD) pattern revealed that, all the compositions possess single-phase spinel structure. The nano-sized grain structure formation was confirmed by transmission electron microscopy (TEM). The dc electrical resistivity shows the samples are semiconducting in nature. The magnetic measurements showed that the composition Ni(0.6)Zn(0.4)Fe(2)O(4) has maximum saturation magnetization (M(s)) while high coersivity (Hc) for ZnFe(2)O(4). Thermoelectric power measurement study showed that the compounds, with x <= 0.4 are p-type and for x > 0.4 behaves n-type conduction mechanism. (C) 2010 Published by Elsevier B.V.
Keywords: Electron microscopy; Magnetic; Sintering; X-ray diffraction

Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction

Effect of aluminium doping on structural and gas sensing properties of zinc oxide thin films deposited by spray pyrolysis - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2011)
A facile spray pyrolysis route is used to deposit aluminium doped ZnO (AZO) thin films on to the glass substrates. It is observed that on aluminium doping the particle size of ZnO reduces significantly; moreover, uniformity of particle also gets enhanced. Their XRD study reveals that intensity ratio of crystal planes depend on the aluminium doping concentration. The gas response studies of; similar to 800 nm thick Al-doped ZnO films at different operating temperatures show that 5 at% Al-doped ZnO thin film exhibits highest response towards H(2)S gas at 200 degrees C. The results suggest that the gas response strongly depends on the particle size and aluminium doping in the ZnO. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Aluminium; H(2)S sensor; Spray pyrolysis; thin film; Zinc oxide

Low temperature pH dependent synthesis of flower-like ZnO nanostructures with enhanced photocatalytic activity - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Materials Research Bulletin, 2011)
In the present study we have synthesized flower-like ZnO nanostructures comprising of nanobelts of 20 nm width by template and surfactant free low-temperature (4 degrees C) aqueous solution route. The ZnO nanostructures exhibit flower-like morphology, having crystalline hexagonal wurtzite structure with (001) orientation. The flowers with size between 600 and 700 nm consist of ZnO units having crystallite size of similar to 40 nm. Chemical and structural characterization reveals a significant role of precursor: ligand molar ratio, pH, and temperature in the formation of single-step flower-like ZnO at low temperature. Plausible growth mechanism for the formation of flower-like structure has been discussed in detail. Photoluminescence studies confirm formation of ZnO with the defects in crystal structure. The flower-like ZnO nanostructures exhibit enhanced photochemical degradation of methylene blue (MB) with the increased concentration of ligand, indicating attribution of structural features in the photocatalytic properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Defects; Nanostructures; Optical properties; Semiconductor

Optical and photocatalytic properties of single crystalline ZnO at the air-liquid interface by an aminolytic reaction - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Langmuir, 2011)
Crystalline flowerlike ZnO was synthesized by an aminolytic reaction at the air-liquid interface in an aqueous media at an alkaline pH. A thin visible film was formed at the air-liquid interface by self-assembly of flowerlike ZnO. Diffraction studies show rearrangement of the single crystalline units at the air-liquid interface leading to the formation of nanobelts. These nanobelts overlap systematically to form petals of the flowerlike structure; individual petals get curved with time. Each nanobelt is found to be single crystalline and can be indexed as the hexagonal ZnO phase. The organic product formed in the aminolytic reaction and dissolution-reprecipitation mechanism is the driving force for the formation of flowerlike ZnO at the air-liquid interface. A clear relationship between the surface, photocatalytic, and photoluminescent properties of ZnO is observed. The flowerlike structure exhibits a blue shift (3.56 eV) in the band emission as compared to bulk ZnO (3.37 eV). The photodegradation of methylene blue over the flowerlike ZnO catalyst formed at the air-liquid interface and in the sediments shows enhanced photocatalytic activity. The sub-bands formed due to surface defects facilitate separation of charge carriers increasing their lifetime, leading to enhanced photocatalytic activity of flowerlike ZnO.

Photoelectrochemical applications of In2Se3 thin films by chemical deposition - Hankare, P. P.; Rathod, K. C.; Asabe, M. R.; Jadhav, A. V.; Helavi, V. B.; Chavan, Santosh S.; Garadkar, K. M.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Indium selenide films have been synthesized by chemical bath deposition method onto stainless steel plate. The configuration of fabricated cell is n-In2Se3| NaOH(1 M) + S(1 M) + Na2S(1 M) |C-(graphite). Characterization of the photoelectrochemical cell was carried out by studying X-ray diffraction, current-voltage and capacitance-voltage characteristics in the dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that the In2Se3 thin films are n-type semiconductor. The junction ideality factor was found to be 3.24. The flat band potential and the barrier height were found to be 0.720 V and 0.196 eV, respectively. From the study of power output characteristics, open circuit voltage, short circuit current, fill factor and efficiency were found to be 310 mV, 20 mu A, 37.64 and 0.61%, respectively. Photoresponse studies show that the lighted ideality factor is 2.78. Maximum current was observed at 575 nm.

Synthesis and characterization of chemically deposited nickel substituted CdSe thin film - Hankare, P. P.; Jadhav, B. V.; Chate, P. A.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2011)
The technologically important Cd(0.5)Ni(0.5)Se thin film has been developed by solution growth technique on non-conducting glass substrate in tartarate bath containing Cd(+2), Ni(+2) ions and sodium selenosulphate in an aqueous alkaline medium at room temperature. Various preparative conditions of the thin films are outlined. The films were characterized by X-ray diffraction, scanning electron microscope, optical absorption and electrical measurements. The X-ray diffraction study indicates that the film is polycrystalline in nature with hexagonal phase. Scanning electron micrograph shows that the film is homogeneous with well-defined grains. The films have high optical absorption coefficient. Thermoelectric power measurement shows p-type conduction mechanism. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Crystal growth; Electrical conductivity; thin film

Synthesis and characterization of cobalt substituted zinc ferri-chromites prepared by sol-gel auto-combustion method - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Patil, R. P.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Mixed metal oxides having spinel structure shows interesting structural properties. In the present investigation, cobalt substituted zinc ferri-chromites were prepared by sol-gel auto-combustion method. The completion of solid state reaction and the formation of spinel phase were identified using X-ray diffraction technique. All the compounds exhibit cubic spinel symmetry and lattice constant shows an irregular trend with substitution of Co. Infra-red spectral studies shows an two strong bands, one around 600 cm(-1) which is attributed to the intrinsic vibrations of tetrahedral complexes and the other at 400 cm(-1) is due to octahedral one. The morphology and size of the particles was found out by scanning electron microscopy while the elemental compositions by elemental dispersive X-ray spectroscopy. The various compounds of the present system Zn1-xCoxFeCrO4 were also investigated for their thermal and electronic studies.

Synthesis of cube-shaped gold nanostructures by electron irradiation - Dhumale, Vinayak A.; Gangwar, Rajesh K.; Shah, Preeti V.; Bhoraskar, Vasant N.; Mulla, Imtiaz S.; Sharma, Rishi B. (Materials Letters, 2011)
The needle-like gold nanostructures were synthesized by using chloroauric acid (HAuCl(4)) as a metal precursor and sodium borohydride (NaBH(4)) as the reducing agent. These needle-like nanostructures of gold were irradiated with high energy electrons (E-6 MeV, phi similar to 10(12) e cm(-2) s(-1)). The pre- and post-irradiated gold nanostructures were characterized by Scanning Electron Microscopy (SEM), UV-vis spectroscopy, X-ray Diffraction (XRD) and contact angle measurement (GBX-Model Digidrop) techniques. The results of the SEM revealed that after electron irradiation, the needle-like gold structures got fragmented into identical cube-shaped gold nanostructures, though of different sizes. The XRD analysis indicated that the average crystallite size of the gold nanostructures remained unchanged even after irradiation with high energy electrons. A glass surface showed hydrophilic behavior when coated with needle-like nanostructures and became ultra hydrophilic when coated with cube-shaped gold nanostructures. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Gold nanostructures; High energy electron irradiation; Nanostructured materials; Radiation damage; Surfaces; Ultra hydrophilic surfaces

Synthesis of single crystalline CdS nanocombs and their application in photo-sensitive field emission switches - Chavan, Padmakar G.; Badadhe, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Nanoscale, 2011)
Single crystalline CdS nanocombs were synthesized by a thermal evaporation route. The photo-sensitive field emission current shows a reproducible switching behavior, with a rise in current level of nearly five times the initial preset value of similar to 1 mu A. An ultra low turn-on field, required to draw an emission current density of similar to 0.1 mu A cm(-2) (100 nA), is found to be similar to 0.26 V mu m(-1) (260 V), which is much lower than the reported values for various other CdS nanostructures. Upon illumination with visible light the CdS nanocombs act as a photo field emission switch. At an applied field of similar to 0.65 V mu m(-1) the current densities are observed to be similar to 14.6 mu A cm(-2) and similar to 26.9 mu A cm(-2), without and with light illumination, respectively. The average emission current is seen to be stable over the duration of measurement for two preset values. The high sensitivity and fast response in the visible range indicates that the CdS nanocombs can be used as a photo-sensitive field emitting switch in device applications, and also in pulsed electron beam technology.

Chemical deposition of CuInSe2 thin films by photoelectrochemical applications - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2012)
Copper indium diselenide films have been synthesized by chemical bath deposition method. The configuration of fabricated cell is n-CuInSe2|NaOH (1 M) + S (1 M) + Na2S (1 M)|C-(graphite). The photoelectrochemical cell characterization of the films is carried out by studying current-voltage characteristics in dark, capacitance-voltage in dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that CuInSe2 thin films are n-type conductivity. The junction ideality factor is found to be 3.81. The flat band potential is found to be 0.763 V. The barrier height value is found to be 0.232 eV. The study of power output characteristic shows open circuit voltage, short circuit current, fill factor and efficiency are found to be 310 mV, 20 mu A, 42.12% and 0.82%, respectively. Photoresponse shows lighted ideality factor which is 2.92. Spectral response shows the maximum current observed at 650 nm. (C) 2011 Published by Elsevier B.V.
Keywords: Chemical bath deposition; Flat band potential; Photo response; Power output; Spectral response

Influence of Pd-loading on gas sensing characteristics of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Nanocrystalline pristine and 0.5, 1.5 and 3.0 wt% Pd loaded SnO2 were synthesized by a facile co-precipitation route. These powders were screen-printed on alumina substrates to form thick films to investigate their gas sensing properties. The crystal structure and morphology of different samples were characterized by using X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The 3.0 wt% Pd:SnO2 showed response of 85% toward 100 ppm of LPG at operating temperature of 250 degrees C with fast response (8 s) and quick recovery time (24 s). The high response toward LPG on Pd loading can be attributed to lowering of crystallite size (9 nm) as well as the role of Pd particles in exhibiting spill-over mechanism on the SnO2 surface. Also selectivity of 3.0 wt% Pd:SnO2 toward LPG was confirmed by measuring its response to other reducing gases like acetone (CH3COCH3), ethanol (C2H5OH) and ammonia (NH3) at optimum operating temperature. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: LPG sensor; Palladium; SnO2; Thick film

Studies on the resistive response of nickel and cerium doped SnO2 thick films to acetone vapor - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Undoped and Ni, Ce-doped nanocrystalline tin oxide were synthesized by co-precipitation route. Doped as well as undoped SnO2 compositions revealed single phase structure without any impurity. The lattice constant of SnO2 increases and the grain size decreases with doping of Ni and Ce. The responses of the sensing elements are evaluated by measuring the resistance change upon exposure to various test gases such as liquid petroleum gas (LPG), acetone, ethanol and ammonia. In comparison to LPG, ethanol, and ammonia the response towards acetone vapor increases markedly on simultaneous doping of Ni and Ce. For acetone vapors with 500 ppm at 300 degrees C, the undoped SnO2 shows 31% response, while with individual Ni or Ce doping it increases to 38 and 60%, respectively, however with simultaneous doping of Ni and Ce there is a significant enhancement up to 92%. The results of gas sensing measurements reveal that the thick films deposited on alumina substrates using screen printing technique give selectively a high response of (87%) with fast recovery (similar to 1 min) towards 100 ppm acetone at 300 degrees C. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: (Ni plus Ce)-doping; Acetone vapor; Screen-printing; SnO2

Acetone vapour sensing characteristics of undoped and Zn, Ce doped SnO2 thick film gas sensor - Bagal, L. K.; Patil, J. Y.; Bagal, K. N.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Materials Research Innovations, 2013)
The nanocrystalline materials of zinc and ceria doped tin oxide [(Zn+Ce)-SnO2] powders were synthesised by coprecipitation method and investigated for their sensing properties towards liquid petroleum gas (LPG), ethanol, ammonia and acetone vapour. The crystal structure and phase of the as synthesised and sintered powders were characterised by X-ray diffractometer and the microstructure by scanning electron microscopy. All the doped and undoped SnO2 compositions revealed single phase solid solution formation. Transmission electron microscope results indicated that well crystallised (Zn+Ce) doped SnO2 particles of size similar to 7 nm were obtained at the annealing temperature of 650 degrees C. The reduction in grain size of the metal oxide is a key factor to enhance the gas sensing properties. The doping of zinc, ceria in SnO2 has reduced the grain size and improved the gas response. The results of gas sensing measurements showed that the thick films deposited on alumina substrates using screen printing technique exhibited high response to acetone at an operating temperature of 300 degrees C. Further, the selectivity of the sensor towards acetone with respect to other reducing gases (LPG, ethanol and ammonia) was studied.
Keywords: Gas; Screen printing; Sensor; SnO2

Liquefied petroleum gas sensing performance of cerium doped copper ferrite - Khandekar, M. S.; Tarwal, N. L.; Patil, J. Y.; Shaikh, F. I.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2013)
Undoped and cerium (Ce) doped nanocrystalline copper ferrite (CuFe2O4) materials were synthesized via the molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CuFe2O4 ferrite have been investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CuFe2O4. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Moreover, the gas sensing properties of sintered samples were studied towards different reducing gases such as liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sample with 4% cerium doped CuFe2O4 (Ce4) showed the maximum gas sensitivity (86%) towards LPG with fast response time of 5 s and good recovery time of 68 s. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrite; Gas sensor; Molten-salt method; TEM

Response to the comments on `Investigations on Ru doped ZnO: strain calculations and gas sensing study' - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2013)

CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis

Nanocrystalline Ce doped CoFe2O4 as an acetone gas sensor - Khandekar, M. S.; Tarwal, N. L.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2014)
Nanocrystalline CoFe2-xCexO4 ferrites (x=0, 0.04, 0.08) were synthesized by using the inexpensive, simple and eco-friendly molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CoFe2O4 ferrite were investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CoFe2O4. Transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Furthermore, the gas response of nanocrystalline ferrite materials was investigated in the temperature range of 200-450 degrees C toward the reducing gases like liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sensor response was found to be sensitive and selective toward acetone as compared to other reducing gases. It is observed that the addition of Ce (4 wt%) strongly influenced the response and the operating temperature of the sensor material and thus can serve as acetone-sensing sensors. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: CoFe2O4; Ferrite; Gas sensor; Molten-salt method; TEM

Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
27th International Vacuum Nanoelectronics Conference (IVNC), Engelberg, SWITZERLAND, JUL 06-10, 2014
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Effect of Pd and Ce on the enhancement of ethanol vapor response of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Vaishampayan, M. V.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Sensors and Actuators B-Chemical, 2015)
The undoped SnO2 and 4 wt% Ce-doped SnO2 were successfully synthesized by a facile co-precipitation route. The ternary systems were prepared by Pd-loading (0.5, 1.5 and 3.0 wt%) on the 4 wt% Ce-doped SnO2 nanoparticles. The structure and morphology of the nanocrystalline powders were investigated by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The nanocrystalline powders were screen printed on the alumina substrates to form thick films to investigate their gas response properties. The gas response studies reveal that 4 wt% Ce-doped SnO2 with the loading of 3.0 wt% Pd exhibits high response (88%) towards ethanol (100 ppm) at an operating temperature of 250 degrees C with quick response (6 s) and rapid recovery (20 s). The high ethanol vapor response at lower operating temperature of this sensor is attributed to the spill-over mechanism of Pd particles present on the SnO2 surface and enhancement in alkalescence of SnO2 due to Ce-doping. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ce-doped tin oxide; Gas sensor; Semiconductor; Thick film

High performance single crystalline PbWO4 nanorod field effect transistor - Walke, Pravin S.; Patil, Vandana B.; Mulla, Imtiaz S.; Late, Dattatray J. (Journal of Materials Science-Materials in Electronics, 2015)
The highly crystalline PbWO4 nanorods were synthesized using simple co-precipitation method which has application in field effect transistor. The synthesized PbWO4 nanorods were characterized by XRD, Raman spectroscopy, TEM and HRTEM indicating highly crystalline nature. Field effect transistor was fabricated on pre-patterned 300 nm SiO2/Si substrates using photolithography technique with channel length 1 A mu m and width 20 A mu m. Thin film (similar to 100 nm) was made up of PbWO4 nanorods by spin coating on the pre-patterned device used as channel layer. The field effect mobility was observed to be 4.7 cm(2) V-1 s(-1) and I-ON/OFF ratio similar to 10(3) which is far better than the organic molecules due to single crystalline nature and rod like morphology of the PbWO4 providing direct path for charges to transport towards channel.

Single SnO2 Nanowire: field emission investigations - Joshi, D.; Joag, Dilip S.; Mulla, Imtiaz S.; Late, Dattatray J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by simple thermal evaporation method. For the realistic analysis of the Fowler Nordheim plot of the semiconducting SnO2, field emission behavior of a single nanowire is studied. A relevant model explaining the field emission mechanism from the single SnO2 nanowire is also proposed by the authors.
Keywords: SnO2 nanowire

SnS2 nanoflakes for efficient humidity and alcohol sensing at room temperature - Bharatula, Lakshmi Deepika; Erande, Manisha B.; Mulla, Imtiaz S.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report a one step facile hydrothermal synthesis of layered SnS2 nanoflakes. The as-synthesized nanosheets are characterized using X-ray diffraction, Raman spectroscopy and Transmission Electron Microscopy (TEM). The humidity sensing behavior of SnS2 nanoflake sensor device were investigated in the range of 11-97% of relative humidity (RH) at room temperature. The response time of similar to 85 s and recovery time of similar to 6 s were observed for the SnS2 nanoflake based humidity sensor. A maximum sensitivity of 11.300% is recorded. We also investigate the SnS2 nanoflake based alcohol sensing properties towards methanol, ethanol and iso-propyl alcohol. An exclusive selectivity towards methanol with a response of 1580 is shown as compared to other analytes. The response time of similar to 67 s and recovery time of just 5 s were observed for the SnS2 nanoflake based methanol sensor.

Nonlinear Fowler-Nordheim behavior of a single SnO2 nanowire - Joshi, Padmashree D.; Joag, Dilip S.; Late, Dattatray J.; Mulla, Imtiaz S. (Journal of Vacuum Science & Technology B, 2017)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by a simple thermal evaporation method. The randomly oriented multiple nanowires grown by the vapor-liquid-solid mechanism exhibit low turn on field (0.8V/mu m defined for the current density of 1 mu A/cm(2)) and linear Fowler-Nordheim nature (FN). However, for the understanding of the nature of the FN plot, field emission behavior of a single SnO2 nanowire is investigated. The FN plot is observed to be nonlinear in nature. A simple model explaining the field emission mechanism from the semiconducting single SnO2 nanowire is proposed. (C) 2017 American Vacuum Society.

Ru, Pd doped WO3 nanomaterials: a synergistic effect of noble metals to enhance the acetone response properties - Kodam, Pavan M.; Ghadage, Pandurang A.; Nadargi, Digambar Y.; Shinde, K. P.; Mulla, Imtiaz S.; Park, J. S.; Suryavanshi, Sharad S. (Ceramics International, 2022)
Noble metals (NMs) have an enormous impact on the intrinsic properties of the metal oxides. We report the synergistic effect of Ruthenium (Ru) and Palladium (Pd) noble metals on the enhancement of gas sensing properties of pure tungsten oxide (WO3). The gas sensing material is synthesized by simple and straight forward precipitation route, and its physico-chemical analyses are determined using XRD, FESEM, TEM/HRTEM, FFT, UV-Vis, XPS, EDAX, and BET measurements. Use of the developed material as a gas sensor is evaluated using several target gases (oxidizing as well as reducing), with acetone showing the best selectivity. The noble metal doping and hence catalytic action improved the gas response qualities. The synergistic effect of Ru and Pd on WO3 gas response properties are identified, where the effect is 99.80% sensitivity, and lower response/recovery time (10 s and 2 min) at 300 degrees C operating temperature. Nonetheless, the sensors displayed better gas sensing properties even at lower operating temperatures ranging from 200 to 275 degrees C. In addition, the synergistic effect has displayed the dramatic enhancement in the sensitivity to 76.44% at barely 10 ppm acetone concentration. This particular result will undoubtedly be helpful for diagnostic purpose of diabetic patients, and a strong candidate for prospective gas sensing applications, particularly acetone.
Keywords: Acetone vapours; Precipitation route; Ru -Pd doping; synergistic effect; WO3

La-Fe-O perovskite based gas sensors: recent advances and future challenges - Patil, Suraj S.; Babar, Bapuso M.; Nadargi, Digambar Y.; Shaikh, Faiyyaj I.; Nadargi, Jyoti D.; Sankapal, Babasaheb R.; Mulla, Imtiaz S.; Tamboli, Mohaseen S.; Truong, Nguyen Tam Nguyen; Suryavanshi, Sharad S. (ACS OMEGA, 2024)
Keywords: ASSISTED SYNTHESIS; ETHANOL SENSING CHARACTERISTICS; LAFEO3 NANOPARTICLES

Reduced graphene oxide/tungsten oxide (rGO/WO3): a versatile nanocomposite for enhanced detection of acetone - Patil, Abhijeet P.; Gaikwad, Mayur A.; Nadargi, Jyoti D.; Shaikh, Hamid; Alam, Mohammad Asif; Tamboli, Mohaseen S.; Kim, Jin Hyeok; Mulla, Imtiaz S.; Suryavanshi, Sharad S. (Journal of Materials Science-Materials In Electronics, 2024)
In this study, we report a straightforward method for synthesizing semi-cubical nanostructures of tungsten trioxide (WO3) loaded with reduced graphene oxide (rGO) via a hydrothermal approach. Furthermore, the systematic investigations were made towards the improved gas sensing capabilities of these nanostructures for acetone. The use of semi-cubical rGO/WO3 nanostructures demonstrate the provision of efficient gas diffusion routes via a meticulously arranged mesoporous framework. Hence, it leads to a significant improvement in the sensing response towards acetone. The analysis of the sensing capabilities demonstrates that the response of the sensor is influenced by variations in operating temperature and gas concentration. It is seen that the inclusion of rGO not only enhances the sensing response but also gives quick response and recovery, which are measured to be 12 and 33 s, respectively. The WO3 sensor loaded with 0.1 wt% rGO demonstrates a discerning reaction to acetone, exhibiting a high response of 93.60% than that of the unmodified WO3 sensor (76.30%). The gas sensing properties are explained through the role of rGO and the structural and morphological properties of the developed nanostructures.

Dual-functional LaFeO3 perovskites via auto-combustion and hydrothermal methods for gas sensing and photocatalytic dye degradation - Patil, Suraj S.; Shinde, Kiran P.; Patil, Abhijeet P.; Abbas, Muhammad Aoun; Nadargi, Jyoti D.; Mujawar, Sarfraj H.; Mulla, Imtiaz S.; Kim, K. B.; Suryavanshi, Sharad S. (Inorganic Chemistry Communications, 2025)
Integrated environmental remediation is increasingly focused on the development of multifunctional materials capable of simultaneous detection of toxic gases and wastewater treatment. Present study aims to develop dual-functional LaFeO3 perovskites for gas sensing and photocatalytic dye degradation. The nanocrystalline powders of LaFeO3 were synthesized via two distinct methods; auto-combustion (A-LFO) and hydrothermal (H-LFO). Numerous characterization techniques (e.g. XRD, SEM, EDAX, BET, TEM, and XPS) were utilized in order to study the phase, morphology, surface area and elemental composition of A-LFO and H-LFO samples. Both samples were systematically evaluated for their potential in the gas sensing and photocatalytic degradation of malachite green (MG). In results, A-LFO exhibited superior performance in both applications, compared to the H-LFO. It shows similar to 90 % sensitivity for the acetone (500 ppm) at the operating temperature of 275 degrees C and achieved similar to 78 % degradation efficiency for malachite green (MG) dye (5 ppm) within 2 h irradiation of natural sunlight. Although, H-LFO presented comparatively lower performance, both materials demonstrated good selectivity, and stability highlighting their promise as a dual-functional environmental remediation agent. By exploring the performance of the synthesized materials in these dual applications, this research established a relationship between synthesis methods, material properties, and overall performance in environmental and industrial applications, by offering a sustainable and efficient solution to complex pollution challenges.
Keywords: Dye degradation; Gas sensing; LaFeO3; Malachite Green; Perovskites

Surfactant-assisted tungsten oxide for enhanced acetone sensing and solar-driven photocatalysis: exploring the role of surfactants - Patil, Abhijeet P.; Patil, Suraj S.; Tamboli, Mohaseen S.; Damkale, Shubhangi R.; Nadargi, Digambar Y.; Nadargi, Jyoti D.; Mulla, Imtiaz S.; Suryavanshi, Sharad S. (RSC Advances, 2025)
Surfactants play a pivotal role in the kinetics of nucleation and accretion of nanoparticles in such a way that they serve as a template for the development of nanostructures, consequently influencing the morphology, dimensions, and other surface properties. Herein, we report the influence of cationic and anionic surfactants (CTAB, SDS, PVP and HMT) on the development of pristine WO3 nanostructures and their impact on gas sensing and photocatalytic properties of WO3. The various surfactant-assisted WO3 nanostructures were synthesized via a straightforward hydrothermal route and systematically analyzed using XRD, FESEM-EDAX, TEM/HRTEM, XPS, UV-Vis, and BET measurements. Gas sensing properties of various oxidizing and reducing gases revealed superior selectivity towards acetone. Among the various surfactant-assisted WO3, CTAB/WO3 exhibited an excellent response of 84.84% towards 100 ppm acetone at an optimal operating temperature of 300 degrees C. The CTAB/WO3 sensor exhibited a linear response to acetone at lower concentrations, showing a 4.8% response at 0.8 ppm, which delineates the threshold between healthy and diabetic breath acetone levels. At 1.8 ppm, the sensor recorded 8.1% response, aligning with diabetes values reported by National Institute for Occupational Safety and Health (NIOSH). Moreover, photocatalytic performance evaluations demonstrated a methylene blue degradation efficiency of 47.19% under natural solar irradiation. This work will motivate researchers in developing high performance acetone gas sensors and photocatalytic dye-degradation by the integration of appropriate surfactants in WO3 nanostructures.